Taxing the Digital Economy. Is the DST the Right Solution - Allevato, Giulio; De Vito, Antonio (SEFO, 2020)
This paper examines the current income tax challenges of the Digital Economy, and the current proposals to tax digital firms where the users of their products or services are located. Building on law and economic literature, the paper firstly reviews the theory on corporate taxation, paying attention to the evidence on tax avoidance and profit shifting of multinational firms. The paper then argues that introducing a new tax on digital businesses could prove ineffective and lead to several distortions on corporate decision-making, especially in the case of unilateral and uncoordinated implementation.
Keywords: Tax policy; Digital services tax; Multinational firms; Digital economy; 53 Ciencias Económicas::5311 Organización y dirección de empresas ::5311.02 Gestión financiera; ODS 8 - Trabajo decente y crecimiento económico